Haemophilus (actinobacillus) pleuropneumoniae infection in germfree piglets - N V Anderson; C A King (Kansas Agricultural Experiment Station Research Reports, 1987)
Germfree piglets rapidly develop pneumonia after Haemophilus pleuropneumoniae is inoculated into the lung, providing a basis of comparison for future studies of pneumonia in SPF and conventionally reared piglets.; Swine Day, Manhattan, KS, November 19, 1987
Keywords: Swine day; 1987; Kansas Agricultural Experiment Station contribution; no. 88-125-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 528; Swine; Haemophilus pleuropneumoniae